“Fortalecimiento de la marca empresarial del restaurante de comida típica Mama Lola a través de estrategias multisensoriales - Torres Quezada, Ana Michelle (2021)
As an object of study, “Mama Lola” establishment was chosen due to being a restaurant that offers traditional food from Loja with 10 years of experience in service, but with a family tradition of more than 80 years. The general objective of the research is to strengthen the business brand of “Mama Lola” restaurant establishment through multisensory strategies, for the fulfillment of the same three specific objectives are proposed: to carry out a diagnosis on the dimensions of the service environment of the “Mama Lola” establishment, to analyze the consumer perception of the dimensions of the “Mama Lola” establishment's service environment and, lastly, propose multisensory strategies that allow strengthening the Mama Lola establishment's brand. To prepare the first objective, an interview was conducted with the manager about the dimensions in terms of service environment, another interview with the chef for the gustatory dimension, and two interviews with the service staff on the social dimension. Subsequently, files of the dimensions of the field service environment were made and finally these results were compared with the arguments of expert authors in sensory marketing. As a result, it was obtained that the establishment maintains a relationship between the concept, mission and vision that the brand proposes and is reflected in each dimension. In the second objective, a survey of 28 questions was applied to a sample of 391 customers, related to the visual, auditory, olfactory, taste and social dimensions, in order to know the consumer's perception of these dimensions. The results were favorable, since the highest percentage of consumers have a perception of positive feelings about the dimensions of the service environment of this restaurant, distributed as follows: within the percentage of 81% -100% are the elements: space, decoration, lighting, construction materials, tone of voice of the staff, taste of the product, texture of the product, color of the product, aroma of the product, experience of the product and treatment by the staff; within the percentage of 61% -80% the elements: arrangement of the furniture, facade of the premises, colors inside the restaurant, music, volume of music and aromas perceived in the rooms; the last range corresponds to 41% -60% where the elements of informational signs, colors of the staff uniform and noise inside the premises were located. For the development of the third objective, a strategic SWOT and SWOT matrix was made from the results obtained in the interviews, technical worksheets of the service environment and literary review (internal analysis) and the application of the consumer perception survey on the dimensions of the service environment of the “Mama Lola” establishment (external analysis). Being the multisensory strategies seven; promote the “Mama Lola” brand and attract customers to the establishment through digital 11 media, training for personal growth of the work team improving the service and operation of the restaurant, reinforcement of informative signs through sensory means to make them more attractive to the public, design of the staff uniform highlighting the colors of the business brand, in order to increase customer appreciation for the brand through the sense of smell, alliances with restaurants within the area to supply the service in high seasons and finally agreements with parking lots near the restaurant. It is concluded that the congruent planning of the dimensions of the service environment has a great impact on the perception of the client since it manages to generate positive sensations in a global way, allowing an experience of the brand. It is recommended to maintain quality standards in all dimensions of the service environment since a failure in any of them can reduce the profitability of the company and consider the suggested strategies at the end of the investigation.